Burnished : Zulu Ceramics between Rural and Urban South Africa - Perrill, Elizabeth (Book collections on Project MUSE., 2022)
-- Showcases the lives and work of individual Black South African artists, mostly women, whose contributions and accomplishments have not been well recognized. --Offers the most complex and richest analysis of Zulu beer pots to date, by examining their history and significance from multiple vantage points, ranging from the art market to the aesthetics and family connections of individual potters. --Approaches Zulu pottery making not to define a normative style but to treat ceramic production as an important mode of self-definition for Zulu women.